Sustainable management of surface substrate layer based on soil microbial diversity during wheat growth season - Li, Aorui; Zhang, Zhimin; Sun, Tianyu; Han, Sheng; He, Yaning; Fan, Huimin; Wang, Hui; Chen, Jiping; Wang, Chi; Ji, Huawei (Bangladesh Journal of Botany, 2025)
High-throughput sequencing technology was used to systematically analyze the composition, diversity, and dynamic changes of soil microbial communities during the wheat growing season in Lintong, Shaanxi Province. The abundance of bacterial communities significantly increases after the complete planting cycle of wheat, while the fungal community structure was relatively stable. At the phylum level, Proteobacteria, Acidobacteria, Bacteroidetes, and Actinobacteria constitute the dominant bacterial communities. The fungal community was Ascomycota and Zygomycota. The growth process of wheat significantly changes the structural composition of bacterial communities, enhances enzyme activity and biological regulatory functions of bacterial communities, while inhibiting cellular processes and environmental information processing functions. This study revealed the succession pattern of soil microbial communities during the wheat growing season, identified key microbial groups that maintain soil ecosystem functions, and provided an important theoretical basis and practical guidance for the sustainable management of the surface substrate layer in the study area. Bangladesh J. Bot. 54(3): 741-748, 2025 (September) Special